Procedure for proofing miracles on the example of miracles through the cause of st. Stanisław Papczyński - Szewczyk, Roman (Prawo Kanoniczne, 2024)
The Church, among its countless followers, declares some blessed and saints by means of the act of those exercising authority in the Church. This act materializes in beatification and canonization. The Church places the statement of holiness, which is a theological reality, in a legal framework, setting specific limits within which this supernatural reality is recognized from the human point of view. Before the Pope announces a miracle, proof and proof are necessary to obtain absolute and complete moral certainty as to the authenticity of a given phenomenon. The article presents an outline of the canonization procedure as a necessary element to declare a person blessed or saint Father Stanisław Papczyński successfully underwent this procedure, which confirmed many works considered inexplicable from a scientific point of view.